Application Progress and Practical Evaluations of Nanofiber Nonwoven Fabrics for Flexible/wearable Batteries. Issue 12 (21st December 2022) - Zhao, Hong; Lam, Wai-Yu Ashley; Ao, Keng long; Xian, Yue; Ren, Yaqi; Si, Liping; Wei, ZhaoHuan; Wang, Jian; Daoud, Walid A.
Abstract : The growing interest in wearable electronics has triggered an enormous demand for flexible/wearable power sources. Flexible batteries, including lithium-ion batteries, Sodium-ion batteries, and Zinc/Zinc-Air batteries have been developed greatly. Nanofiber nonwoven fabrics form highly porous networks with remarkable interconnectivity between their pores, making them play an important role in flexible batteries as separators, current collectors, electrodes, etc. It looks that nanofiber nonwoven fabrics are promising to apply in flexible batteries, thus it is time to summarize their fabrication technology, flexible characteristics, electrochemical performance, and application prospects. This review paper focused on the current application status, emerging developments, and challenges of nanofiber nonwoven fabrics produced by electrospinning on flexible batteries. It is hopeful that this job will provide important references for the flexible batteries industrialization.